e-Dictionaries-based Semantic Gradient: Assisting Preschool Children Connect between Known and New Vocabulary - Yohannes Telaumbanua; Nurmalina Nurmalina (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2022)
The accuracy of selecting learning strategies and the intensive uses of e-dictionaries in Early Childhood Education are the critical points of interest in enhancing preschool children’s linguistic intelligence and digital skills. The facts are both have not yet been priority scales in the children’s ELT programs, however. This study, therefore, aimed at diagnosing the effects of this research on the children’s linguistic intelligence and digital skills. Observation and field-note were the techniques of collecting the data, the (Bogdan Biklen, 2006) model was a technique of data analysis while triangulation was used to verify the data. The 25 preschool children were judgementally selected as research participants. The finding indicated that this study practically affects the children’s linguistic intelligence of “word smarts, “lexical meaning smarts,” “semantic meaning smarts” and “grammatical word order smarts,” “digital awareness,” “digital competence,” “critical thinking skills (HOTS),” and 4C skills. In conclusion, this research enables the children to make connections between known and new words, to distinguish shades of word’s meaning, help them become word choosy, and ease them to gradually understand spoken and written language along with the abilities to talk and write themselves. It also enhances the children knowledge and understanding of related lexis and vocabulary skills, assists them to make connection and predictions, and improve comprehension.